Prediction ability in bilingual individuals: an eye tracking study with younger and older adults - Ribu, Ingeborg Sophie; Simonsen, Hanne Gram; Norvik, Monica; Lehtonen, Minna; Murstad, Jeanett; Theimann, Ane; Nygreen, Thomas; Goral, Mira (Springer Science and Business Media LLC, 2025)
Studies with monolingual speakers show that people predict upcoming linguistic elements during sentence processing. Linguistic prediction behavior has been found to be less consistent in studies with bilingual individuals performing in their non-native language and in neurotypical older monolingual adults. The present study utilized an eye-tracking paradigm to investigate whether bilingual younger and older neurotypical individuals predict upcoming nouns in sentences that include constraining verbs, and if they do so both in their first language (L1) and in their second language (L2). Data were analyzed from 44 Norwegian-English proficient bilingual adults; 27 younger (20–35 years, mean age 27) and 17 older adults (54–81 years, mean age 64) who completed the eye-tracking experiment in each of the two languages, as well as cognitive and linguistic tests. The results demonstrated similar prediction abilities in L1 and L2 for both the younger and older participants on sentences with constraining verbs. Older adults predicted slower than younger adults. Participants’ working memory span and language proficiency did not explain prediction performance; cognate status of the stimuli partially did. The study adds to the relatively sparse existing data on prediction abilities in bilingual people and in older individuals.